Swarm-dular quadcopter: bringing swarm robotics and modular robotics together - Mohan, Deepak; R. Guruprasad, K (International Journal of Engineering and Technology, 2018)
In this paper, we present a new concept in robotics, which we call as swarm-dular robotics, by bringing together swarm robotics and modular robotics. We propose a swarm-dular quadcopter, which is a  modular  quadcopter, where, multiple wheeled  ground robots (AGVs), which  are part of a heterogenous swarm or  multi-robotic(agent) system (MRS or MAS), attach/dock  together to form an aerial quadcopter robot. We provide a conceptual design and demonstrate the proposed system using simulation experiments in  Robot Operating System (ROS). Behavior of the system as both a swarm and a modular quadcopter UAV are demonstrated.